2015
DOI: 10.3389/fbioe.2015.00086
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Bilateral Symmetry During Manual Wheelchair Propulsion

Abstract: Studies of manual wheelchair propulsion often assume bilateral symmetry to simplify data collection, processing, and analysis. However, the validity of this assumption is unclear. Most investigations of wheelchair propulsion symmetry have been limited by a relatively small sample size and a focus on a single propulsion condition (e.g., level propulsion at self-selected speed). The purpose of this study was to evaluate bilateral symmetry during manual wheelchair propulsion in a large group of subjects across di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 32 publications
3
26
1
10
Order By: Relevance
“…It is also known that dominant side has a higher capacity to loss temperature and better thermoregulation [65], getting cold in response to the onset of the activity because of the vasoconstriction effect. This is not reflected in our results and it can be due to the bilateral propulsion of the wheelchair that may compensate this asymmetry in WCUs [66]. Finally, Shin-ichi et al [26] found a nonuniform distribution of the temperature in the bust rising heterogeneously during both wheelchair exercise and recovery, which is consistent with our lack of pattern in DT sk after exercise.…”
Section: Discussionsupporting
confidence: 80%
“…It is also known that dominant side has a higher capacity to loss temperature and better thermoregulation [65], getting cold in response to the onset of the activity because of the vasoconstriction effect. This is not reflected in our results and it can be due to the bilateral propulsion of the wheelchair that may compensate this asymmetry in WCUs [66]. Finally, Shin-ichi et al [26] found a nonuniform distribution of the temperature in the bust rising heterogeneously during both wheelchair exercise and recovery, which is consistent with our lack of pattern in DT sk after exercise.…”
Section: Discussionsupporting
confidence: 80%
“…That said, the side‐to‐side differences in PO warrant future study with respect to whether this occurred at the start of the sprint (eg, problems with hand‐to‐tire coupling) or toward the end of the sprint (eg, fatigue effects); whether the symmetry noted was due to the type of health condition (eg, SCI vs non‐SCI); and/or whether there was asymmetric dynamic loading of the rollers. Nevertheless, the results of this study highlight the need to gather information on bilateral symmetry particularly if there are issues with secondary injury or pain . It is also unknown at present whether WCR players would be at a higher risk of shoulder pain from these side‐to‐side asymmetries on the court or even whether these asymmetries exist during daily ambulation in day‐chair wheelchair‐user combinations.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, the results of this study highlight the need to gather information on bilateral symmetry particularly if there are issues with secondary injury or pain. 12,23 It is also unknown at present whether WCR players would be at a higher risk of shoulder pain from these side-to-side asymmetries on the court or even whether these asymmetries exist during daily ambulation in day-chair wheelchair-user combinations. Consequently, these results are of interest to strength and conditioning practitioners as training regimes must address these side-to-side asymmetries alongside the tailored programs that are often prescribed to develop the posterior muscle groups.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data was previously collected from 223 individuals with complete motor paraplegia while they propelled their wheelchair at a self-selected speed on a stationary ergometer that simulated level propulsion over a tile surface (e.g., Soltau et al, 2015). The subjects were recruited from outpatient clinics throughout the Rancho Los Amigos National Rehabilitation Center, and informed written consent was obtained in accordance with the governing Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%